Pgrmc1: new roles in the microglial mediation of progesterone-antagonism of estradiol-dependent neurite sprouting and in microglial activation - Bali, Namrata; Morgan, Todd E.; Finch, Caleb E. (Frontiers in Neuroscience, 2013)
Pgrmc1 expression in microglia was recently shown by the present authors to mediate estrogen-progesterone interactions during axonal sprouting and to mediate microglial activation itself. We discuss these findings in relation to other functions of Pgrmc1 in the nervous system and its possible relationship to the sigma-2 receptor .